Hepatocellular Carcinoma Challenges and Opportunities of a Multidisciplinary Approach - Tsoulfas, Georgios (IntechOpen, 2022)
Hepatocellular carcinoma (HCC) represents one of the most significant global health issues, given its high prevalence and the challenging nature and physiology of the liver and hepatic surgery, in its many forms. This means that the most appropriate management for HCC should incorporate a multidisciplinary approach, combining the expertise from several different specialties. This book showcases the various steps in the development, diagnosis, staging, and management of HCC and provides views and thoughts from true experts in the field. As such, it is a useful resource for any physician or surgeon, whether training or practicing, who is interested in caring for patients with HCC.